PricewaterhouseCoopers guide to charitable giving - Kennedy, Michael B. (John Wiley, 2002)
Get the Most Out of Giving with PricewaterhouseCoopers' Guide to Charitable Giving Private philanthropy is the cornerstone of charitable organizations in the United States. This support provides numerous benefits to society as well as a tax-efficient means for you, the donor, to transfer wealth. Understanding the tax implications of your donations can be confusing as well as financially detrimental if you do not have the proper guidance. PricewaterhouseCoopers' Guide to Charitable Giving addresses the many tax aspects of charitable giving by walking you through the rules of charitable giving and their relationship to your taxes. This indispensable guide explores different charitable giving alternatives, focusing on current gifts, deferred or planned gifts, gifts of income, annuities, and charitable bequests. It also covers the advantages and disadvantages of each type of gift, as well as funding alternatives and assets that may be utilized. The charitable giving strategies discussed are supplemented with essential forms, their instructions, and relevant IRS publications. The charitable advice and strategies offered by PricewaterhouseCoopers professionals outline some of the best ways to give in a timely and tax-efficient manner. Take this opportunity to understand the tax implications of your charitable donations and learn how to get the most out of giving.